Pengaruh Faktor Makro Ekonomi, Dana Pihak Ketiga dan Pangsa Pembiayaan Terhadap Profitabilitas Industri Perbankan Syariah di Indonesia Tahun 2011-2015 - Laras Andasari Syachfuddin; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to determine the effect of macroeconomics factor, third party funds and market share to profitability sharia banks industry period 2011 until 2015. The research method used is a quantitative approach. The dependent variable in this study is profitability (ROA), as well as the independent variable in this study is macroeconomics factor (inflation and gross domestic product), third party funds and market share. Sampling method in this research used a saturated sampling. The analysis technique used is multiple linier regression.Research result shows that the confidence level is 95%, macroeconomics factor (inflation and gross domestic product) and third party funds have a negative correlation to profitability (ROA). Simultaneously variables in this study a significant effect on the magnitude of the amount of profitability (ROA) sharia banks industry with 84.4% value of coefficient determination. The partially, third party funds and market share had significant effect toprofitability (ROA) sharia banks industry.